Pengaruh Waktu ElektroplatingCu-Mn Terhadap Laju Korosi Baja AISI 1020 Dalam Medium Korosif NaCl 3% - Ratna Noviyana; Ediman Ginting Suka; Yayat Iman Supriyatna (Jurnal Teori dan Aplikasi Fisika, 2017)
The influence of electroplating time Cu-Mn to corrosion rate of Steel AISI 1020 in corrosive medium NaCl 3% had been researched. Corrosion rate testing is used weight loss method by soaking the samples in the corrosive medium NaCl for 168 hours. The results showed that the longer time electroplating that used, the corrosion rate will be decreased. This is because the growing number of Cu and Mn ions deposited on the surface of the sample after electroplating. The lowest corrosion rate obtained at the time of 50 seconds that is 0.098 mmpy. The analysis results of metallurgical microscope showed that the coating looks thicker with increasing time of electroplating, while after corrosion rate tested thecoatings being black and a few coating of samples were cracked due to corrosion.The X-Ray Diffraction (XRD) characterization result showed thatthe phase of AISI 1020 raw material after corrosion tested is changed from pure iron (Fe) to magnetite phase (Fe3O4).